PENDETEKSIAN BAKTERI Raistonia solanacearum, Yabuuchi et al 1995 MENGGUNAKAN TEKNIK REAKSI POLIMERASE BERANTAI DAN PEMBEDAAN STRAIN MENGGUNAKAN TEKNIK HIBRIDISASI DNA - Yadi Suryadi; M Machmud; MA Suhendar (BERITA BIOLOGI, 2000)
Raistonia solanacearum,the bacterial wilt pathogen, has a wide host range and genetic variability.Rapid and sensitive molecular techniques need to be developed for eariy detection and strain differentiation of the pathogen.Molecular techniques such as PCR and DNA hybridization have been succesfully used to detect and identify bacterial plant pathogens including R.solanacearum.These techniques were adopted under Indonesian condition, using purified and crude DNA from infected plant samples.An R.solanacearum specific DNA primer (OH/Y2) was used in the PCR test,and a DNA probe 5a67 were used in the non-radioactive hybridization test.The PCR techniqe could be used to detect R.solanacearum from infected plant samples in less than 5 hours.The DNA hybridization technique was applicable to differentiate strains ofR.solanacearum into three groups based on their DNA profiles.